Large-scale preparation method of piezotransparent micro-nano fiber film capable of visually monitoring interfacial pressure distribution

Multi-layer ultra-thin press-transparent micro-nano fiber films were prepared by electrospinning and combined with color or fluorescent film substrates, which solved the problem of low resolution of existing PCM films and achieved high-resolution pressure monitoring.

CN119610825AActive Publication Date: 2025-03-14SUN YAT SEN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411806816.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-14
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

The existing pressure-chromic material (PCM) films have low resolution during pressure monitoring, making it difficult to accurately monitor the pressure information of micro-nano interfaces.

Method used

Electrospinning method is used to prepare multi-layer ultra-thin press-transparent micro-nano fiber films, and are combined with color films or cesium lead fluorescent film substrates to form separate press-chromic materials that visually monitor the interface pressure distribution.

Benefits of technology

The pressure monitoring resolution is significantly improved, so that the film can stably and conveniently present different transparency under different pressures, and accurately record pressure information.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119610825A_ABST
    Figure CN119610825A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of material science, in particular to a large-scale preparation method of a pressure-induced transparent micro-nano fiber film capable of visually monitoring interfacial pressure distribution. The multi-layer ultrathin pressed transparent film constructed by micro-nano fibers layer by layer is prepared by taking plastic macromolecules such as polyacrylonitrile and polymethyl methacrylate as raw materials through an electrostatic spinning method. After being pressed, irreversible plastic deformation induces the disappearance of interlayer and intra-layer pores to guide the change of a light scattering path so as to cause irreversible transparency conversion, and a long-term stable pressure information recording capability is provided; and the piezochromic film can be combined with a color film or a cesium lead bromide fluorescent film and other substrates to obtain a new-structure piezochromic film which can be separated and combined as required, the pressure monitoring resolution is obviously improved, and the piezochromic film has the advantages of real-time performance, convenience, stability, applicability and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of material science and technology, and in particular to a large-scale preparation method of a pressure-induced transparent micro-nano fiber film for visually monitoring interface pressure distribution. Background Art

[0002] Electrical signal pressure monitoring has excellent response speed and sensitivity, but the complex preparation process (micro-nano processing), high cost (electronic devices and arraying), harsh and restricted testing conditions and dependence on the collaborative work of multiple devices seriously hinder its practical application.

[0003] Pressure-induced chromic materials (PCMs) are a new type of intelligent materials that change color significantly under pressure, including pressure-induced fluorescent chromic materials, pressure-induced phosphorescent chromic materials, and pressure-induced transparent materials. In recent years, researchers have used PCM to present different color characteristics under different pressures, and used the color change rate to correlate the size and distribution of interface pressure, that is, to obtain a two-dimensional real-time map of the size and distribution of micro-nano interface pressure in real time through the color change rate. Most PCMs are prepared with polymers as the main body, without the need for multiple equipment to coordinate, which reduces the manufacturing cost. In addition, PCM does not require external drive or reading circuits, is simple and convenient to use, and has low testing requirements. Usually PCM does not contain electronic components and electrodes, and high-voltage in-situ monitoring will not affect the stability of pressure sensing, and has excellent robustness. The unique advantages of PCM make it have important application value in the fields of pressure sensing, information storage, interface pressure monitoring, product anti-counterfeiting, and optoelectronic devices. Especially in high-end manufacturing, assembly, security inspection, and acceptance are heavily dependent on the pressure feedback provided by PCM.

[0004] At present, PCM is mainly divided into four categories: organic fluorescent small molecules represented by spiropyran, one-dimensional photonic crystals such as cellulose nanocrystals, covalent organic metal frameworks with conformational conversion, and color-changing microcapsule composite films. Microcapsule composite films are currently the only commercial PCM films, such as the pressure-sensitive film developed by Foxconn in Japan, but the color change after the capsule ruptures is instantaneous and randomly diffuse, making it difficult to continuously and accurately record pressure information. The spatial resolution of the pressure-sensitive film can only reach 100μm, which is far from meeting the requirements for accurately monitoring micro-nano interface pressure information.

[0005] Therefore, based on the above-mentioned related technologies, it is urgent to develop a large-scale preparation method for pressure-induced transparent micro-nano fiber film for visually monitoring interface pressure distribution. Summary of the invention

[0006] In view of this, the purpose of the present invention is to propose a large-scale preparation method of a pressure-induced transparent micro-nano fiber film for visually monitoring interface pressure distribution, so as to solve the problem of low resolution of PCM membrane in the pressure monitoring process in the prior art.

[0007] Based on the above objectives, the present invention provides a method for large-scale preparation of pressure-induced transparent micro-nano fiber films for visually monitoring interface pressure distribution.

[0008] A method for large-scale preparation of a pressure-induced transparent micro-nano fiber film for visually monitoring interface pressure distribution comprises the following steps:

[0009] Step S1. Add a plastic polymer to an organic solvent, heat and stir to mix evenly, and obtain a polymer solution A;

[0010] Step S2. Testing and recording the viscosity and surface tension of the polymer solution A, and adjusting the diameter of the electrospun fiber in combination with the electrospinning parameters, thereby adjusting the pressure detection range of the micro-nano fiber film;

[0011] Step S3. Add the polymer solution A into the electrospinning syringe, push the syringe piston until no bubbles escape from the solution, turn on the electrospinning device, set the spinning parameters, and obtain a layer-by-layer micro-nano fiber film. The prepared film is white and opaque;

[0012] Step S4. Prepare a color film or fluorescent film substrate, and prepare a separate piezochromic material by bonding the micro-nano fiber film and the substrate. The preparation method of the cesium lead bromide fluorescent film substrate is as follows: dissolve cesium bromide and lead bromide in polymethyl methacrylate and N,N-dimethylformamide (25%) respectively, and control the concentration of cesium bromide and lead bromide to 1%-5%, and fully mix them to obtain a mixed solution; take a clean glass sheet, put it on the adsorption table of a high-speed spin coater, preheat the mixed solution to 70°C, take a small amount and drop it on the glass sheet and rotate it at high speed to obtain a spin-coated film; transfer the spin-coated film to a hot stage at 80°C, anneal for 2 minutes, and the volatilization of N,N-dimethylformamide induces the formation of cesium lead bromide nanocrystals, thereby obtaining a cesium lead bromide film with uniform fluorescent green light;

[0013] Step S4. A masked photolithography method established in the laboratory is used to prepare a mold with a surface microstructure, wherein the microstructure is a stripe pattern, and a mold with different stripe spacing is obtained by controlling the photolithography mask and etching conditions to obtain a pressure monitoring resolution;

[0014] Step S5. Use Solidworks and other software modeling combined with 3D printing to build a ring-shaped uniform light source (ultraviolet light and sunlight) to obtain a two-dimensional pressure distribution map;

[0015] The high molecular polymer in step S1 is any one of plastic polymers such as polyacrylonitrile, polymethyl methacrylate or polyvinyl butyral. The pressure detection range can be adjusted according to the modulus of the polymer used.

[0016] Preferably, the polymer is a plastic hydrophobic polymer with a molecular weight of 104 -10 5 g / ml, a micro-nano fiber film with good fiber morphology can be obtained by using a suitable molecular weight.

[0017] Preferably, the organic solvent in step S1 is obtained by mixing N,N-dimethylformamide and acetone in a mass ratio of 6.5-7.5:2.5-3.5;

[0018] The mass ratio of the polymer compound to the organic solvent is 1-3:7-20;

[0019] The temperature during the heating and stirring is 50-70° C., and the stirring rate is 260-320 rpm.

[0020] Preferably, the diameter of the electrospinning syringe in step S3 is 8-10 cm, and the injection speed is 0.8-1.2 mL / h;

[0021] Among the spinning parameters, the positive electrode voltage of the electrostatic field is 6-15 kv, the negative electrode voltage is 2-3 kv, the rotating speed of the collecting roller is 80-200 rpm, the distance between the spinning nozzle and the collecting roller is 10-20 cm, and the spinning time is 1-5 h.

[0022] Preferably, the thickness of the micro-nano fiber film in step S3 is 20-60 μm.

[0023] Beneficial effects of the present invention:

[0024] The present invention provides a large-scale preparation method of a pressure-induced transparent micro-nano fiber film for visually monitoring interface pressure distribution. The method utilizes the principle of irreversible plastic deformation of plastic polymers when they are under pressure, and uses polyacrylonitrile or polymethyl methacrylate plastic polymers as raw materials to prepare a multi-layer ultra-thin pressure-induced transparent film constructed layer by layer of micro-nano fibers through an electrospinning method. The film can be combined with a substrate such as a color film or a cesium lead bromide fluorescent film to obtain a new structure pressure-induced chromic film that can be separated and combined as needed, and the pressure monitoring resolution is significantly improved.

[0025] Polyacrylonitrile and polymethyl methacrylate plastic polymers have intrinsic plasticity and hydrophobicity, and have good stability in the film; and the prepared multi-layer ultra-thin pressure-transparent film constructed layer by layer of micro-nano fibers has a thickness of 20-60μm. The layered assembly of the internal polymer fibers and the pore structure between the fibers make it have multiple scattering properties for light and appear opaque. However, under pressure induction, the internal polymer fiber layer gradually disappears, and the disappearance of the pores between and within the layers allows light to pass evenly, reducing the multiple scattering of light and making it present different transparencies under different pressures. This irreversibility enables it to accurately record pressure information.

[0026] The separated piezochromic film prepared by the piezo-transparent micro-nano fiber film and the cesium lead bromide film substrate can continuously and stably change color in the air and has ultra-high resolution. The advantages of real-time, convenience, stability and applicability combined with the scalability, scale potential and high resolution of the preparation make the present invention have a wider application prospect compared with the existing technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 The micro-nano fiber film prepared in Example 1 and Example 2 of the present invention;

[0029] Figure 2 The scanning electron microscope images of the internal pore structure of the micro-nano fiber film prepared in Example 1 and Example 2 of the present invention before and after the application of pressure;

[0030] Figure 3 is the transparency of the micro-nano fiber film prepared in Example 1 and Example 2 of the present invention measured by ultraviolet transmission spectrum after applying different pressures;

[0031] Figure 4 The transparency and fluorescence transmittance of the micro-nano fiber film combined with the cesium lead bromide film prepared in Example 1 of the present invention under different applied pressures;

[0032] Figure 5 This is the resolution of the micro-nano fiber film combined with the cesium lead bromide film prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0033] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0034] The sources and properties of some of the raw materials used in the present invention are as follows:

[0035] Polymethyl methacrylate was purchased from Dongguan Fulin Plastic Raw Materials Co., Ltd.; polyacrylonitrile was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; N,N-dimethylformamide was purchased from Nantong Zhonghe Chemical New Materials Co., Ltd.; and acetone was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0036] Example 1: A method for large-scale preparation of a pressure-induced transparent micro-nano fiber film for visually monitoring interface pressure distribution, comprising the following steps:

[0037] S1. 1 g of polyacrylonitrile having a molecular weight of 60,000 g / mol was added to 7 g of an organic solvent, wherein the organic solvent was obtained by mixing 6.5 g of N,N-dimethylformamide and 3.5 g of acetone, heated to 50 ° C, and mixed at a stirring rate of 320 rpm to obtain a polymer solution A;

[0038] S2. Add polymer solution A into an electrospinning syringe with a diameter of 10 cm at an injection rate of 0.8 mL / h, push the syringe piston until no bubbles escape from the solution, turn on the electrospinning device, set the electrostatic field positive voltage to 7 kV, the negative voltage to 2 kV, the collection drum speed to 80 rpm, the spacing between the spinning nozzle and the collection drum to 18 cm, and the spinning time to 1 h to obtain a pressure-induced transparent micro-nano fiber film;

[0039] Step S3. Prepare a color film or fluorescent film substrate, and prepare a separate piezochromic material by bonding the micro-nano fiber film obtained in step S2 to the substrate, wherein the preparation method of the cesium lead bromide fluorescent film substrate is as follows: dissolve cesium bromide and lead bromide in polymethyl methacrylate and N,N-dimethylformamide (25%) respectively, control the concentration of cesium bromide and lead bromide to 1%-5%, and mix them thoroughly; take a clean glass sheet, put it on the adsorption table of a high-speed spin coater, preheat the mixed solution to 70°C, take a small amount and drop it on the glass sheet and rotate it at high speed to obtain a spin-coated film; transfer the spin-coated film to a hot stage at 80°C, anneal for 2 minutes, and the volatilization of N,N-dimethylformamide induces the formation of cesium lead bromide nanocrystals, thereby obtaining a cesium lead bromide film with uniform fluorescent green light;

[0040] Step S4. Using a masked photolithography method established in the laboratory to prepare a mold with a surface microstructure, wherein the microstructure is a stripe pattern, for obtaining a pressure monitoring resolution;

[0041] Step S5. Use software such as Solidworks to build a model combined with 3D printing to build a ring-shaped uniform light source (ultraviolet light and sunlight) to obtain a two-dimensional pressure distribution map.

[0042] Example 2: A method for large-scale preparation of a pressure-induced transparent micro-nano fiber film for visually monitoring interface pressure distribution, comprising the following steps:

[0043] S1. Add 1 g of polymethyl methacrylate having a molecular weight of 15000 g / mol to 7 g of an organic solvent, wherein the organic solvent is obtained by mixing 7 g of N,N-dimethylformamide and 3 g of acetone, heating to 55° C., and mixing at a stirring rate of 300 rpm to obtain a polymer solution A;

[0044] S2. Add polymer solution A into an electrospinning syringe with a diameter of 10 cm at an injection rate of 0.9 mL / h, push the syringe piston until no bubbles escape from the solution, turn on the electrospinning device, set the electrostatic field positive voltage to 7.5 kv, the negative voltage to 2.5 kv, the collection drum speed to 90 rpm, the spacing between the spinning nozzle and the collection drum to 18 cm, and the spinning time to 4.5 h to obtain a pressure-induced transparent micro-nano fiber film;

[0045] S3. Prepare a color film or fluorescent film substrate, and prepare a separate piezochromic material by bonding the micro-nano fiber film obtained in step S2 to the substrate, wherein the preparation method of the cesium lead bromide fluorescent film substrate is as follows: dissolve cesium bromide and lead bromide in polymethyl methacrylate and N,N-dimethylformamide (25%) respectively, control the concentration of cesium bromide and lead bromide to 1%-5%, and mix them thoroughly; take a clean glass sheet, put it on the adsorption table of a high-speed spin coater, preheat the mixed solution to 70°C, take a small amount and drop it on the glass sheet and rotate it at high speed to obtain a spin-coated film; transfer the spin-coated film to a hot stage at 80°C, anneal for 2 minutes, and the volatilization of N,N-dimethylformamide induces the formation of cesium lead bromide nanocrystals, thereby obtaining a cesium lead bromide film with uniform fluorescent green light;

[0046] S4. A mold with a surface microstructure is prepared by a masked photolithography method established in the laboratory, wherein the microstructure is a stripe pattern, which is used to obtain pressure monitoring resolution;

[0047] S5. Use Solidworks and other software modeling combined with 3D printing to build a circular uniform light source (ultraviolet light and sunlight) to obtain a two-dimensional map of pressure distribution.

[0048] Example 3: A method for large-scale preparation of a pressure-induced transparent micro-nano fiber film for visually monitoring interface pressure distribution, comprising the following steps:

[0049] S1. Add 2 g of polyvinyl butyral having a molecular weight of 90,000 g / mol to 15 g of an organic solvent, wherein the organic solvent is obtained by mixing 7 g of ethanol and 3 g of water, heating to 60 ° C, and mixing at a stirring rate of 280 rpm to obtain a polymer solution A;

[0050] S2. Add polymer solution A into an electrospinning syringe with a diameter of 10 cm at an injection rate of 1 mL / h, push the syringe piston until no bubbles escape from the solution, turn on the electrospinning device, set the electrostatic field positive voltage to 7.5 kv, the negative voltage to 2.5 kv, the collection drum speed to 100 rpm, the spacing between the spinning nozzle and the collection drum to 19 cm, and the spinning time to 4 h to obtain a pressure-induced transparent micro-nano fiber film;

[0051] S3. Prepare a color film or fluorescent film substrate, and prepare a separate piezochromic material by bonding the micro-nano fiber film obtained in step S2 to the substrate, wherein the preparation method of the cesium lead bromide fluorescent film substrate is as follows: dissolve cesium bromide and lead bromide in polymethyl methacrylate and N,N-dimethylformamide (25%) respectively, control the concentration of cesium bromide and lead bromide to 1%-5%, and mix them thoroughly; take a clean glass sheet, put it on the adsorption table of a high-speed spin coater, preheat the mixed solution to 70°C, take a small amount and drop it on the glass sheet and rotate it at high speed to obtain a spin-coated film; transfer the spin-coated film to a hot stage at 80°C, anneal for 2 minutes, and the volatilization of N,N-dimethylformamide induces the formation of cesium lead bromide nanocrystals, thereby obtaining a cesium lead bromide film with uniform fluorescent green light;

[0052] S4. A mold with a surface microstructure is prepared by a masked photolithography method established in the laboratory, wherein the microstructure is a stripe pattern, which is used to obtain pressure monitoring resolution;

[0053] S5. Use Solidworks and other software modeling combined with 3D printing to build a circular uniform light source (ultraviolet light and sunlight) to obtain a two-dimensional map of pressure distribution.

[0054] Example 4: A method for large-scale preparation of a pressure-induced transparent micro-nano fiber film for visually monitoring interface pressure distribution, comprising the following steps:

[0055] S1. 2 g of polystyrene having a molecular weight of 80,000 g / mol was added to 15 g of an organic solvent, wherein the organic solvent was 13 g of N,N-dimethylformamide, heated to 65 ° C, and mixed at a stirring rate of 260 rpm to obtain a polymer solution A;

[0056] S2. Add mixture B into an electrospinning syringe with a diameter of 10 cm at an injection rate of 1.1 mL / h, push the syringe piston until no bubbles escape from the solution, turn on the electrospinning device, set the electrostatic field positive voltage to 8 kV, the negative voltage to 3 kV, the collection drum speed to 110 rpm, the spacing between the spinning nozzle and the collection drum to 19 cm, and the spinning time to 3 h to obtain a pressure-induced transparent micro-nano fiber film;

[0057] Step S3. Prepare a color film or fluorescent film substrate, and prepare a separate piezochromic material by bonding the micro-nano fiber film obtained in step S2 to the substrate, wherein the preparation method of the cesium lead bromide fluorescent film substrate is as follows: dissolve cesium bromide and lead bromide in polymethyl methacrylate and N,N-dimethylformamide (25%) respectively, control the concentration of cesium bromide and lead bromide to 1%-5%, and mix them thoroughly; take a clean glass sheet, put it on the adsorption table of a high-speed spin coater, preheat the mixed solution to 70°C, take a small amount and drop it on the glass sheet and rotate it at high speed to obtain a spin-coated film; transfer the spin-coated film to a hot stage at 80°C, anneal for 2 minutes, and the volatilization of N,N-dimethylformamide induces the formation of cesium lead bromide nanocrystals, thereby obtaining a cesium lead bromide film with uniform fluorescent green light;

[0058] Step S4. Using a masked photolithography method established in the laboratory to prepare a mold with a surface microstructure, wherein the microstructure is a stripe pattern, for obtaining a pressure monitoring resolution;

[0059] Step S5. Use software such as Solidworks to build a model combined with 3D printing to build a ring-shaped uniform light source (ultraviolet light and sunlight) to obtain a two-dimensional pressure distribution map.

[0060] Example 5: A method for large-scale preparation of a pressure-induced transparent micro-nano fiber film for visually monitoring interface pressure distribution, comprising the following steps:

[0061] S1. Add 3 g of polyvinylidene fluoride having a molecular weight of 15000 g / mol to 20 g of an organic solvent, wherein the organic solvent is obtained by mixing 7.5 g of N,N-dimethylformamide and 3.5 g of acetone, heating to 70 ° C, and mixing at a stirring rate of 260 rpm to obtain a polymer solution A;

[0062] S2. Add polymer solution A into an electrospinning syringe with a diameter of 10 cm at an injection rate of 1.2 mL / h, push the syringe piston until no bubbles escape from the solution, turn on the electrospinning device, set the electrostatic field positive voltage to 8 kV, the negative voltage to 3 kV, the collection drum speed to 120 rpm, the spacing between the spinning nozzle and the collection drum to 20 cm, and the spinning time to 2 h to obtain a pressure-induced transparent micro-nano fiber film;

[0063] S3. Prepare a color film or fluorescent film substrate, and prepare a separate piezochromic material by bonding the micro-nano fiber film obtained in step S2 to the substrate, wherein the preparation method of the cesium lead bromide fluorescent film substrate is as follows: dissolve cesium bromide and lead bromide in polymethyl methacrylate and N,N-dimethylformamide (25%) respectively, control the concentration of cesium bromide and lead bromide to 1%-5%, and mix them thoroughly; take a clean glass sheet, put it on the adsorption table of a high-speed spin coater, preheat the mixed solution to 70°C, take a small amount and drop it on the glass sheet and rotate it at high speed to obtain a spin-coated film; transfer the spin-coated film to a hot stage at 80°C, anneal for 2 minutes, and the volatilization of N,N-dimethylformamide induces the formation of cesium lead bromide nanocrystals, thereby obtaining a cesium lead bromide film with uniform fluorescent green light;

[0064] S4. A mold with a surface microstructure is prepared by a masked photolithography method established in the laboratory, wherein the microstructure is a stripe pattern, which is used to obtain pressure monitoring resolution;

[0065] S5. Use Solidworks and other software modeling combined with 3D printing to build a circular uniform light source (ultraviolet light and sunlight) to obtain a two-dimensional map of pressure distribution.

[0066] Example 6: A method for large-scale preparation of a pressure-induced transparent micro-nano fiber film for visually monitoring interface pressure distribution, comprising the following steps:

[0067] S1. Add 3 g of polycarbonate having a molecular weight of 15000 g / mol to 20 g of an organic solvent, wherein the organic solvent is obtained by mixing 7.5 g of dichloromethane and 3.5 g of N,N-dimethylformamide, heating to 70 ° C, and mixing at a stirring rate of 260 rpm to obtain a polymer solution A;

[0068] S2. Add polymer solution A into an electrospinning syringe with a diameter of 10 cm at an injection rate of 1.2 mL / h, push the syringe piston until no bubbles escape from the solution, turn on the electrospinning device, set the electrostatic field positive voltage to 8 kV, the negative voltage to 3 kV, the collection drum speed to 120 rpm, the spacing between the spinning nozzle and the collection drum to 20 cm, and the spinning time to 2 h to obtain a pressure-induced transparent micro-nano fiber film;

[0069] S3. Prepare a color film or fluorescent film substrate, and prepare a separate piezochromic material by bonding the micro-nano fiber film obtained in step S2 to the substrate, wherein the preparation method of the cesium lead bromide fluorescent film substrate is as follows: dissolve cesium bromide and lead bromide in polymethyl methacrylate and N,N-dimethylformamide (25%) respectively, control the concentration of cesium bromide and lead bromide to 1%-5%, and mix them thoroughly; take a clean glass sheet, put it on the adsorption table of a high-speed spin coater, preheat the mixed solution to 70°C, take a small amount and drop it on the glass sheet and rotate it at high speed to obtain a spin-coated film; transfer the spin-coated film to a hot stage at 80°C, anneal for 2 minutes, and the volatilization of N,N-dimethylformamide induces the formation of cesium lead bromide nanocrystals, thereby obtaining a cesium lead bromide film with uniform fluorescent green light;

[0070] S4. A mold with a surface microstructure is prepared by a masked photolithography method established in the laboratory, wherein the microstructure is a stripe pattern, which is used to obtain pressure monitoring resolution;

[0071] S5. Use Solidworks and other software modeling combined with 3D printing to build a circular uniform light source (ultraviolet light and sunlight) to obtain a two-dimensional map of pressure distribution.

[0072] Example 7: A method for large-scale preparation of a pressure-induced transparent micro-nano fiber film for visually monitoring interface pressure distribution, comprising the following steps:

[0073] S1. Add 3 g of polyphenylene ether having a molecular weight of 15000 g / mol to 20 g of an organic solvent, wherein the organic solvent is obtained from chloroform, heat to 70 ° C, and mix at a stirring rate of 260 rpm to obtain a polymer solution A;

[0074] S2. Add polymer solution A into an electrospinning syringe with a diameter of 10 cm at an injection rate of 1.2 mL / h, push the syringe piston until no bubbles escape from the solution, turn on the electrospinning device, set the electrostatic field positive voltage to 8 kV, the negative voltage to 3 kV, the collection drum speed to 120 rpm, the spacing between the spinning nozzle and the collection drum to 20 cm, and the spinning time to 2 h to obtain a pressure-induced transparent micro-nano fiber film;

[0075] S3. Prepare a color film or fluorescent film substrate, and prepare a separate piezochromic material by bonding the micro-nano fiber film obtained in step S2 to the substrate, wherein the preparation method of the cesium lead bromide fluorescent film substrate is as follows: dissolve cesium bromide and lead bromide in polymethyl methacrylate and N,N-dimethylformamide (25%) respectively, control the concentration of cesium bromide and lead bromide to 1%-5%, and mix them thoroughly; take a clean glass sheet, put it on the adsorption table of a high-speed spin coater, preheat the mixed solution to 70°C, take a small amount and drop it on the glass sheet and rotate it at high speed to obtain a spin-coated film; transfer the spin-coated film to a hot stage at 80°C, anneal for 2 minutes, and the volatilization of N,N-dimethylformamide induces the formation of cesium lead bromide nanocrystals, thereby obtaining a cesium lead bromide film with uniform fluorescent green light;

[0076] S4. A mold with a surface microstructure is prepared by a masked photolithography method established in the laboratory, wherein the microstructure is a stripe pattern, which is used to obtain pressure monitoring resolution;

[0077] S5. Use Solidworks and other software modeling combined with 3D printing to build a circular uniform light source (ultraviolet light and sunlight) to obtain a two-dimensional map of pressure distribution.

[0078] Comparative Example 1:

[0079] This comparative example is a commercialized Fuji pressure-sensitive paper purchased from Taobao. The brand is FUJIFILM. The pressure detection range is 0-300MPa, the resolution is greater than 100μm, and the actual measured resolution is between 100-200μm.

[0080] Comparative Example 2:

[0081] Compared with Example 1, the spinning time in this comparative example was only increased to 4 hours, and a micro-nano fiber film was obtained, and its thickness was measured to be 320 μm.

[0082] Comparative Example 3:

[0083] Compared with Example 1, this comparative example only adjusts the concentration of polymer solution A and the electrospinning parameters to obtain a layer-by-layer constructed film with a larger diameter of micro-nano fibers. Scanning electron microscopy results show that the diameter is about 4 μm and the thickness of the obtained film is about 100 microns.

[0084] Comparative Example 4:

[0085] Compared with Example 1, this comparative example only replaces the polymer used with elastic polyvinyl alcohol, the solvent is water, the dissolution condition is 90° C. and stirring is performed for 2 hours, and then the micro-nano fiber film is prepared by electrospinning.

[0086] Performance Test:

[0087] Performance test of pressure-induced transparent micro-nano fiber film:

[0088] A glass slide with a striped micrometer-level pattern was placed on the pressure-transparent micro-nano fiber film prepared in Examples 1-7 and Comparative Examples 1-4, and the film was placed on a mirror substrate, respectively. A pressure test was performed using a universal press, and the test pressure was set to 800N (the pressure value varies according to the modulus of the polymer) and maintained for 20 seconds. The film was removed and observed using a scanning electron microscope;

[0089] Transparency performance test:

[0090] The pressure-induced transparent micro-nano fiber films prepared in Examples 1-7 and Comparative Examples 1-4 were placed in the middle of a mirror pressure head, respectively, and a pressure test was performed at a set pressure using a universal press, and the changes in their transparency were observed under a ring light source and a microscope;

[0091] Transparency performance test after combining with substrate:

[0092] 2g of PMMA and 5g of N,N-dimethylformamide are mixed to obtain an organic solvent, and cesium bromide and lead bromide are dissolved in the organic solvent respectively, wherein the concentration of cesium bromide is 2% and the concentration of lead bromide is 5%, and the two solutions are evenly mixed and heated to 60-70°C, 1-2mL is dropped on a clean glass sheet, and rotated at high speed to obtain a spin-coated film, and the spin-coated film is transferred to a hot stage at 70-80°C, and annealed for 2-3min to obtain a cesium lead bromide film;

[0093] A set pressure was applied to the pressure-induced transparent micro-nano fiber films prepared in Examples 1-7 and Comparative Examples 1-4 using a universal press, and then the pressure-induced transparent ultra-thin films were placed on the cesium lead bromide films for bonding, and microscope pictures were taken under the excitation of sunlight and ultraviolet light to obtain the transparency difference rate;

[0094] Resolution performance test:

[0095] The pressure-transparent micro-nano fiber films prepared in Examples 1-7 and Comparative Examples 1-4 were combined with cesium lead bromide films to obtain separate piezochromic films. A set pressure was applied on a universal testing machine, and the films were removed and processed by computer to obtain their resolution images and resolution.

[0096] Pressure detection range test;

[0097] The pressure-induced transparent micro-nano fiber films prepared in Examples 1-7 and Comparative Examples 1-4 were respectively subjected to a certain pressure in the range of 0-2000N using a mirror pressure head on a universal testing machine to detect the pressure detection range of different micro-nano fiber films.

[0098] Table 1

[0099]

[0100]

[0101] Data Analysis:

[0102] As can be seen from Table 1, the pressure-induced transparent micro-nano fiber film for visual monitoring of interface pressure distribution prepared by the present invention has higher resolution and greater transparency difference rate. This may be due to the control of polymer solution A and electrospinning parameters, so that the obtained micro-nano fiber film has a lower thickness (20-60μm) and a lower internal fiber diameter (0.5-2.0μm), thereby obtaining a smaller pore size and a higher porosity, and the scattering of light is linearly related to the change in porosity. Films with higher porosity and smaller pore size can sensitively sense changes in different pressures, and thus have higher resolution and transparency difference rate.

[0103] Comparative Example 1 is a commercial Fuji pressure-sensitive paper, the principle of which is that the inside is filled with dye-containing microcapsules, and the capsules are compressed and ruptured, resulting in color changes. The diameter of the microcapsules is micrometer-level, which makes it difficult to obtain a higher resolution due to this structure itself. The measured resolution is greater than 100μm, which poses a challenge to high-resolution pressure distribution imaging. Compared with Example 1, Comparative Example 2 only increases the spinning time to 4h, and the excessive spinning time leads to a higher thickness of the resulting spinning film. The advantage of the present invention is that the film itself is thinner (can be as low as 20μm), which makes it subject to uniform pressure in the entire pressure direction after being compressed, so that the pore structure gradually disappears as a whole, inducing changes in the light scattering path, thereby obtaining a higher resolution. However, when the thickness of the film is high, the local change of the pores in the pressure direction is difficult to cause a complete change in the light scattering path, resulting in a lower resolution. Compared with Example 1, Comparative Example 3 only regulates the diameter of the fibers inside the micro-nano fiber film. The larger diameter makes its modulus higher, thereby increasing the pressure detection range, but the thickness is slightly increased, which reduces its resolution. Comparative Example 4 only replaces the polymer used with elastic, hydrophilic polyvinyl alcohol compared to Example 1, and the obtained micro-nano fiber film has no obvious pressure-induced transparency. This is mainly because the polyvinyl alcohol fibers inside the film have high elasticity, and the deformation caused by pressure is mostly elastic deformation. After the external force is removed, the deformation recovers, resulting in a low rate of change in porosity, making it difficult to induce changes in the scattering path of light. The internal pores cause multiple scattering of light inside, making it difficult for light to pass through the film.

[0104] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

[0105] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A large-scale preparation method of pressure-induced transparent micro-nano fiber film for visually monitoring interface pressure distribution, characterized in that: The following steps are involved: Step S1. Add a plastic polymer to an organic solvent, heat and stir to mix evenly, and obtain a polymer solution A; Step S2. Testing and recording the viscosity and surface tension of the polymer solution A, and adjusting the diameter of the electrospun fiber in combination with the electrospinning parameters, thereby adjusting the pressure detection range of the micro-nano fiber film; Step S3. Add the polymer solution A into the electrospinning syringe, push the syringe piston until no bubbles escape from the solution, turn on the electrospinning device, set the spinning parameters, and obtain a layer-by-layer micro-nano fiber film. The prepared film is white and opaque; Step S4. Prepare a color film or fluorescent film substrate, and prepare a separate piezochromic material by bonding the micro-nano fiber film and the substrate. The preparation method of the cesium lead bromide fluorescent film substrate is as follows: dissolve cesium bromide and lead bromide in polymethyl methacrylate and N,N-dimethylformamide (25%) respectively, and control the concentration of cesium bromide and lead bromide to 1%-5%, and mix them thoroughly to obtain a mixed solution; take a clean glass sheet, put it on the adsorption table of a high-speed spin coater, preheat the mixed solution to 70°C, take a small amount and drop it on the glass sheet and rotate it at high speed to obtain a spin-coated film; transfer the spin-coated film to a hot plate at 80°C and anneal for 2 minutes; Step S4. A masked photolithography method established in the laboratory is used to prepare a mold with a surface microstructure, wherein the microstructure is a stripe pattern, and a mold with different stripe spacing is obtained by controlling the photolithography mask and etching conditions to obtain a pressure monitoring resolution; Step S5. Use Solidworks and other software modeling combined with 3D printing to build a ring-shaped uniform light source (ultraviolet light and sunlight) to obtain a two-dimensional pressure distribution map; The high molecular polymer in step S1 is any one of plastic polymers such as polyacrylonitrile, polymethyl methacrylate or polyvinyl butyral.

2. The method for large-scale preparation of pressure-induced transparent micro-nano fiber film for visually monitoring interface pressure distribution according to claim 1 is characterized in that: The polymer described in step S1 is a plastic hydrophobic polymer with a molecular weight of 10 4 -10 5 g / ml.

3. The method for large-scale preparation of pressure-induced transparent micro-nano fiber film for visually monitoring interface pressure distribution according to claim 1, characterized in that: The organic solvent in step S1 is obtained by mixing N,N-dimethylformamide and acetone in a mass ratio of 6.5-7.5:2.5-3.5; The mass ratio of the polymer compound to the organic solvent is 1-3:7-20; The temperature during the heating and stirring is 50-70° C., and the stirring rate is 260-320 rpm.

4. The method for large-scale preparation of pressure-induced transparent micro-nano fiber film for visually monitoring interface pressure distribution according to claim 1, characterized in that: The diameter of the electrospinning syringe in step S3 is 8-10 cm, and the injection speed is 0.8-1.2 mL / h; Among the spinning parameters, the positive electrode voltage of the electrostatic field is 6-15 kv, the negative electrode voltage is 2-3 kv, the rotating speed of the collecting roller is 80-200 rpm / min, the distance between the spinning nozzle and the collecting roller is 10-20 cm, and the spinning time is 1-5 h.

5. The method for large-scale preparation of pressure-induced transparent micro-nano fiber film for visually monitoring interface pressure distribution according to claim 1, characterized in that: The thickness of the micro-nano fiber film in step S3 is 20-60 μm.

Citation Information

Patent Citations

  • Activated carbon fibers, methods of their preparation, and devices comprising activated carbon fibers

    CA2619829A1

  • Force-sensitive stretchable electro-spinning patterning conductive nanofiber membrane and preparation method thereof

    CN104894750A

  • Flexible sensing composite film with high sensitivity and wide detection range as well as preparation method and application of flexible sensing composite film

    CN115323621A

  • Multi-layer sandwich structure pressure color-changing film and preparation method and application thereof

    CN117774468A

  • Ultrafast water flux through hot-pressed solution blown spun nanofiber-based thin film composite membranes for forward osmosis

    US20230271141A1